Effect of sulphur and iron levels on yield and nutrient content and uptake of Clusterbean [Cyamopsis tetragonoloba (L.) Taub.] in arid region of Rajasthan - Tiwari, D.K.; Pareek, B.L.; Singh, Bahadur (Annals of Agricultural Research, 2017)
A field experiment was conducted on clusterbean during kharif 2012 at Agronomy farm of Swami Keshwanand Rajasthan Agriculture University, Bikaner. There were four levels of sulphur (0, 20, 40 and 60 kg S/ha) and four levels of iron (0, 2.5, 5 and 7.5 kg Fe/ha) carried out to study the effect of sulphur and iron on yield and quality of clusterbean. The results indicated that application of 40 kg S/ha significantly increased yield, nutrient content and uptake of cluster bean and remained at par with 60 kg S/ha. Result further indicated that the application of iron @ 5 kg/ha significantly increased seed, stover and biological yield, nutrient content of cluster bean and remained at par with 7.5 kg Fe ha–1. However, S and Fe uptake in seed and straw and their total uptake significantly higher recorded with 60 kg S/ha and 7.5 kg Fe/ha over all other treatments.